Resultados del primer Vivero Internacional de Rendimiento y Adaptacion de Frijol (Phaseolus vulgaris L.) - Voysest Voysest, Oswaldo (International Center for Tropical Agriculture, 1976)
In 1976 CIAT`s bean program initiated international trials on bean yields and organized the International Bean Yield and Adaptation Nursery (IBYAN) with the following objectives: (a) to evaluate the yield and adaptation of promising germplasm selections under different environmental conditions, representative of the principal bean-producing regions of the world; (b) evaluate the best var. of each region comparing them with the samples of select germplasm; and (c) provide new sources of germplasm so that each region or national program could incorporate them into their breeding program. All the expt. were conducted with the same exptl. design. All the information is presented as tabulated data on the main results, indicating the trials conducted on 25 var. in different agroclimatic regions of the 31 participant countries. Data reported includes: bean yield; harvested plants; days to flowering; growth habit; plant height; lodging; dehiscence, the no, of pods/plant; the wt. of 100 seeds; seed quality; days to physiological maturity; the date of crop maturity and the attack of diseases such as anthracnose, bacterioses, rust, angular leaf spot, web blight, powdery mildew, the complex of root rots, and insect pests found in the different regions. (CIAT)